Perception and practice of junk food consumption among undergraduate students in a medical university in Chengalpattu District” - Gunaseelan Latha Kokilaa; Ravichandhiran Gowthamkarthic; Abhinandan Wali; Soumya Agadi (World Nutrition, 2023)
Introduction Junk foods are defined as processed foods with negligible nutrient value and are often high in salt, sugar, and fat. Junk foods with high sugar content deplete energy levels and the ability to concentrate for extended periods, especially for college students who are forced to consume junk food to curb their hunger as it gives them a sense of pleasure. Due to low prices and affordability, they consume junk food as an alternative to home food.